PENERAPAN METODE KARYAWISATA SEBAGAI UPAYA PENINGKATAN FISIK MOTORIK ANAK - Ati Sulastri; Saeful Millah; Fanny Fauzi Hanifunni’am (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2019)
The gross motor development of a child is related to the ability to use whole body movements to express ideas and feelings and the skill to use hands to create or change things. This gross motor development includes specific physical abilities such as coordination, balance, skills, strength and flexibility. The research method used in this research is the book resech research method or book review and literature study with descriptive analysis. Research uses a qualitative approach. Data collection techniques with descriptive analysis. Research uses a qualitative approach. Data collection techniques with descriptive analysis. There are two things a child might do after observing a field trip; 1). trying to sharpen the impression of his observations so as to clarify the understanding of something, 2). trying to reproduce the things that were observed. Field trips can provide opportunities for young children to develop an interest in something. For example, to develop interest in animals, children can be invited to visit the zoo. As a provision for field trips, children should first be given information in class about several things that will be observed. Information obtained by children is input in further learning activities that will enrich the content of learning activities in class. This connection will clarify the concept he just got: 1). Students can witness firsthand the activities carried out at the site of the visit, 2). students gain stabilization of the theories they have learned in school with the application reality applied to the objects they visit, 3). students can experience the practical experience of a science that has been obtained at school, 4) with field trips various subjects studied at once and integral and not only limited to one subject, 5). can provide satisfaction, 6). can add to the experience of students, and the teacher has a good opportunity to explain an object clearly., 8). train students to be more open, objective and broad in their views of the outside world, and 9). Students can do physical movements so as to stimulate physical improvement in motor skills.